A general property-structure relationship from crack stability analysis on hybrid staggered composites with elasto-plastic matrices. (15th May 2020) - Yu, Zhongliang; Liu, Junjie; Wei, Xiaoding
Abstract: In the present study, fracture analysis is carried out on the representative unit cell of staggered composites consisting of hybrid reinforcements and elasto-plastic matrices. The deformation and failure of hybrid composites are examined through energy-based fracture theory. Analytical formulae for characteristic overlap length, failure strain, and toughness of the unit cell that are related to the properties and geometries of constituents emerge from rigorous derivations. The influences of the matrix plasticity and tablet dissimilarity on the crack stability, the characteristic overlap length, the final failure strain, and toughness are also elucidated. Our study shows that if designed appropriately, the matrix plasticity can effectively improve the material ductility and toughness through crack stabilization. On the other hand, although hybrid reinforcements could effectively tune the ductility, they may cause a loss of material toughness in some cases. More importantly, our model provides guidance to the promising design space where the well-known ductility-strength trade-off dilemma for traditional engineering materials could be resolved.